Sustainable Carbon Cycles: A Framework for the Ramp-up of Carbon Capture? - André Wolf (Intereconomics)
Abstract With its communication “Sustainable Carbon Cycles”, the European Commission has opened a new chapter in European climate policy. For the first time, natural and artificial CO2 capture and storage technologies are to be covered jointly in an overarching regulatory approach. This article reviews the techno-economic potentials of the application fields envisaged by the Commission’s strategy, and defines central requirements for a future funding framework. The establishment of markets for carbon credits is identified as a basis for commercialising storage solutions. However, a prerequisite for efficient trading is to create transparency about the climate impact of the technology alternatives. Efforts to improve existing measurement concepts and test procedures as well as the development of certified standards are decisive steps on this path. The time horizon of carbon sequestration should be a crucial aspect in certification and monitoring. Double funding and unnecessary subsidisation of activities that are already profitable today need to be avoided.